Pengembangan Platform E-Commerce Menggunakan OpenCart untuk Transformasi Pemasaran UMKM di Kecamatan Palupuh - Ariska, Vina; Annas, Firdaus; Alia, Rahma (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This research aims to develop a web-based digital platform using the OpenCart application to optimize the marketing of MSME products in Palupuh District. So far, MSMEs still rely on traditional promotional methods which limit marketing reach and product introduction, both at the local and global levels. In the digital era with rapid technological developments, MSMEs have a great opportunity to expand market reach, increase competitiveness, and support local economic growth through digital platforms. This research uses qualitative methods with a Research and Development (R&D) approach which refers to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research stages include identifying user needs, system design, platform development, to implementation and evaluation with MSME actors. The research results produced a web-based digital platform with intuitive and easy-to-use features, specifically designed to support the marketing of UMKM products. Effectiveness tests show that this platform significantly increases product competitiveness, expands market access, and increases the introduction of UMKM products to the public. With this platform, it is hoped that UMKM in Palupuh District can compete in the modern market and utilize digital technology in a sustainable manner for business development. This research makes a real contribution in supporting the digitalization of UMKM in rural areas.